Reductive Monocarboxylation of Aryl Alkynes with CO2 via Electrochemistry - Zhang, Zhihai; Zhu, Shuping; Wei, Qianqian; Mao, Jianyou; Zhang, Yanhua (Synthesis, 2025)
An electrochemical monocarboxylation of aryl alkynes with carbon dioxide to prepare acrylic acids and propionic acids has been developed. In a three-electrode electrochemical system, the reaction proceeds smoothly at a constant current in acetonitrile, which contains tetrabutylammonium bromide, and gives monocarboxylic acid products with up to 72% overall isolated yield. The system is applicable to terminal and internal aryl alkynes, exhibiting good functional group tolerance. This method may open up a window for the application of the electrochemical strategy in the synthesis of monocarboxylic acids from unsaturated hydrocarbons.
Keywords: Electrochemistry; Aryl alkynes; Reductive monocarboxylation; Carbon dioxide; Organic synthesis